Real-World Application of Insulin Pump Therapy Among Patients With Type 1 Diabetes in China: A Cross-Sectional Study - Huo, Lili; Deng, Wei; Lan, Ling; Li, Wei; Shaw, Jonathan E.; Magliano, Dianna J.; Ji, Linong (Frontiers in Endocrinology, 2022)
Background: Although insulin pump therapy is an important treatment modality for patients with type 1 diabetes, rates of pump use appear to vary broadly internationally. This study aimed to investigate the application of insulin pump therapy among patients with type 1 diabetes in China. Methods: Data were collected from the Type 1 Diabetes Mellitus in China: Coverage, Costs and Care Study (3C Study). A total of 779 participants from this cross-sectional study were included. Multivariable logistic regression was used for data analysis. Results: The median (interquartile range) age at diagnosis of diabetes was 17 (10–28) years and the duration of diabetes was 4 (1–8) years. Among 779 patients, only 89 patients (11.4%) patients used an insulin pump to control blood glucose. A statistically significant difference was found in HbA1c favoring insulin pump therapy (8.3±1.7% vs. 9.2±2.6%) without obvious differences for severe hypoglycaemia. There were higher proportions of patients with no smoking, frequent daily intake of fruits and vegetables, and adequate self-blood glucose monitoring among patients with insulin pump therapy as compared to those using multiple daily insulin injections. Logistic regression analysis showed that younger age at diagnosis, longer duration of diabetes, higher education level of family members, and higher household income were associated with the use of an insulin pump. Conclusions: Data from 3C Study demonstrated that only a minority of patients with type 1 diabetes in China utilize insulin pump therapy. Insulin pump therapy was associated with better blood glucose control and self-management. Patients with younger age at diagnosis and longer duration of diabetes, and patients with better socioeconomic status were more likely to use an insulin pump.